PELESTARIAN BAHASA DAERAH BALI DI ERA GLOBALISASI - Simamora, Nurlaidy Joice (Majalah Ilmiah METHODA, 2023)
Globalization able to make the language of region extinct, it is because nowadays every people expecially youth generation more comfortable using English language than local language. Youth generation think local language is considered lacking. Language shift also supported by social media. That is way government and every people need cooperation in preserving the language of the region. Like using local language as a subject in every school, using local language on the public street billboard or any airport in the major cities. Or also duplicating the flogger or youtuber to preserve the language of the region, because today is social media time. Ths research focuses on the area of Bali, where Bali is a tourist area. It is very strong for the preservation of the language region.